Antibacterial activity of a combination of cysteine and ciprofloxacin and its relationship with the generation of oxidative stress in extended-spectrum betalactamase-producing escherichia coli strains - Martínez, S. R. (2018)
The aim of the present work was to evaluate whether L-cysteine enhances theantibiotic susceptibility of extended-spectrum beta-lactamase (ESBL) Escherichia coli strains to ciprofloxacin and to identify the role of Reactive oxygen species (ROS) in the antimicrobial activity.The combined ef5fect of L-cysteine and ciprofloxacin was investigated by the macrodilution broth method and chemiluminescence assay. ESBL 1 and ESBL 2 strains presented a growth inhibition when they were incubated with 0.4 or 0.2 mM of cysteine, respectively compared to the control without antibiotic. Both strains at sub-inhibitory concentration of ciprofloxacin were combined withcysteine, and a clear growth inhibition respect to the control was observed. An increase of 68% in ROS occurred respect to the control when ESBL 1 was treated with a combination of ciprofloxacin and cysteine, while for ESBL 2 there was a rice of 127 %. The combination of ciprofloxacin with cysteine had the capacity to undergo redox cycling and ROS production with subsequent cellularinjury.